Avaliação da dor oncológica: estudo comparativo com pacientes internados em um hospital de referência em Natal/RN - Costa, Weruska Alcoforado (2010)
Quasi-experimental study, with prospective data, comparative with quantitative approach, performed in a reference hospital, aiming to identify the effectiveness of the Numerical Rating Scale (NRS) and McGill Pain Questionnaire, used simultaneously, to evaluate a group of patients with oncologic pain (Experimental Group); to identify the effectiveness of the Numerical Rating Scale (NRS) to evaluate a group of patients with oncologic pain (Control Group); to identify the resolution of pain according to prescribed medication, considering the result of the rating scales, and to compare it between the two groups of patients in the study. The population consisted of 100 patients, with both the experimental and control groups being composed of 50 people, with data collected from February to April 2010. The results show that in the experimental group, 32% of the patients were aged 60 to 69, 80% were female; 30% had a primary tumor in the breast, 58% had metastasis, and on 70% the disease was localized. In the first pain evaluation, 26% identified it as light; 46%, moderate; and 28%, severe; with an average of 5.50. In the second pain evaluation, 2% reported no pain; 70%, light; 26%, moderate. and 2%, severe, with an average of 3.30. On those with moderate pain, 60% used non-opioid medicine, 25% under severe pain were medicated with non-opioids and 41.67% with weak opioids. Regarding the Pain Management Index (PMI), 44.0% were rated as "-1". In the control group, 28% were aged 40 to 49, and 54% were male; 20% had primary tumor in the breast and genital-urinary system, consecutively; 56% presented metastasis; on 64% the disease was localized. In the first pain evaluation, 14% considered it light; 42%, moderate; and 44%, severe; with an average of 6.26. In the second pain evaluation, 18% did not signal pain; on 38% pain was light; 40%, moderate; and 4%, severe; with an average of 3.0. Regarding medicine therapy, 71.43% with moderate pain used non-opioids, 22.73% with severe pain used non-opioids and 27.27% weak opioids. Considering PMI, 42% were rated "-1"; and 42%, rated "0". We conclude that, despite the importance of pain as the 5th vital sign, it is still under-identified and under-treated by professionals. Nevertheless, studied oncologic patients had a tendency to report pain more easily when evaluated with the NRS instrument than with the combined use of NRS and MPQ. We believe, however, that the combination of these two instruments represents a more effective evaluation of pain, as it allows comprehension of its quantitative and qualitative aspects. We recommend, however, the replication of this study on a larger population, for a longer span of time, and consequently generating more evaluations, so this can confirm or deny the hypothesis that NRS and MPQ can, together, better evaluate pain on the oncologic patient